Of shrub, cactus, vine and toad: psychedelic species of conservation concern - Ermakova, Anna O.; Gandy, Sam (Frontiers in Conservation Science, 2025)
Psychedelics have a profound potential to catalyze psychological transformation and support traditional cultures and ways of life. However, many naturally occurring psychoactive plants and animals are facing threats from climate change, habitat loss and other anthropogenic pressures like overharvesting. In this narrative review we examine the conservation issues pertaining to some of the most well-known naturally occurring psychedelics: peyote (Lophophora williamsii), ayahuasca vine (Banisteriopsis caapi), iboga (Tabernanthe iboga) and the Sonoran Desert toad (Incilius alvarius). For each of the four species we aim to: review their conservation status; assess the sustainability of current sourcing practices; discuss pathways for sustainability of access; examine the efforts underway to preserve these medicines by Indigenous people and local communities; and propose how these efforts could be supported or expanded. This review focuses on an urgent issue of conservation of naturally occurring psychedelic plant and animal species and draws attention to their conservation needs. We conclude that despite biological and ecological differences, all four species face similar knowledge gaps limiting evidence-based conservation. Priorities across species include: long-term ecological and demographic monitoring; genetic and chemical diversity studies; sustainable harvest and management research; integration of Indigenous knowledge and socio-cultural research into conservation frameworks.